AN ANALYSIS OF STUDENTS’ ABILITY IN WRITING SHORT MESSAGE AT EIGHTH GRADE STUDENTS OF SMP NEGERI 4 TANJUNGPINANG - English Education FKIP (Juliet, 2020)
The objective of this study was to know the eighth grade students’ ability in writing short message of SMP Negeri 4 Tanjungpinang. Research design that the researcher used is qualitative descriptive with purposive sampling technique to get the research subject. The subject of the study was the class eight three students of SMP Negeri 4 Tanjungpinang in the Academic Year of 2018/2019, which consisting of 37 students. The researcher got the data by used written test to the students. The researcher used Glass writing assessment to analyze students’ writing ability. But, the researcher just focuses in an aspect, which is organization or structure of the text. The result of this study is the students’ ability in writing is low, specifically writing short message using present continuous tense. This supported by the fact that among 37 students, there were only seven students got high score, five students got moderate score, and twenty five students got low score. Based into the class average percentage, the students in the class eight three (VIII.3) got 49.05%, means insufficient achievement or poor ability.